Teacher as an agent of change in the rural community (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2026)
This scientific article reflects on the role of the teacher as an agent of social change in the rural community of Guanarito, Siquisique Parish, Urdaneta Municipality, Lara State, Venezuela. The main purpose was to reveal, interpret, and understand the experiences and subjective meanings that teachers assign to educational work, understood as a formative process that serves as a strategic pillar of community development. Methodologically, the study was framed within the interpretive paradigm, using a qualitative approach. A phenomenological-hermeneutic method was applied to understand the reality under study. Data were collected through in-depth interviews and focus groups with a purposive sample of three teachers, in order to gain insight into their experiences and perspectives. The findings showed that teaching goes beyond academic instruction and includes the promotion of local culture, the technical management of community projects, and mediation in neighborhood conflict resolution. Social actors view teachers as natural leaders and key drivers of sustainable community development. In conclusion, the role of teachers in Guanarito goes beyond education; they also co-construct social reality, acting as a dialogic bridge between tradition and modernity, and playing a significant role in strengthening community resilience
Keywords: teacher; agent of change; rural community